PERAN AKUNTANSI MANAJEMEN TERHADAP KINERJA UMKM - Nur Diana Kholidah SM; Yulani, Farah Siska; Handayati, Puji; Makaryanawati (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2025)
This scoping review aims to map existing research related to the implementation of management accounting on the performance of MSMEs. The importance of implementing management accounting on the performance of MSMEs needs to be increased both in terms of resources and support from the government. This review refers to five stages, namely: 1) looking for research questions; 2) identify relevant research; 3) selection of articles; 4) data mapping; and 5) compile, summarize and report the results. The time range of the article is 2014-2024. The results of these observations reveal that most research recognizes the role of management accounting in improving the performance of MSMEs. However, there is still the application of management accounting, especially for small and developing MSMEs. Therefore, it is hoped that this research can provide broader insight into the importance of implementing management accounting in the performance of MSMEs.